L’essaimage : une pratique d’enquête au service d’une transition écologique par le bas - Dany Lapostolle; Alex Roy (Développement Durable et Territoires)
In this article, we report on the practices of swarming of local transition initiatives carried out by citizen collectives in the Bourgogne Franche-Comté region. Swarming, defined as a way of investigating in order to act, characterizes an « environmental activism of doing » that is structured in a reticular and translocal way. These multiple initiatives that make everyday gestures a lever for ecological transformation are activated with or without territorial institutions. The latter, independently of the echo they give to these experiments, are challenged in their way of conceiving public action under strong ecological constraints.